2015
DOI: 10.5194/se-6-311-2015
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate breakdown and surface seal development influenced by rain intensity, slope gradient and soil particle size

Abstract: Abstract. Aggregate breakdown is an important process which controls infiltration rate (IR) and the availability of fine materials necessary for structural sealing under rainfall. The purpose of this study was to investigate the effects of different slope gradients, rain intensities and particle size distributions on aggregate breakdown and IR to describe the formation of surface seal. To address this issue, 60 experiments were carried out in a 35 × 30 × 10 cm detachment tray using a rainfall simulator. By sie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 63 publications
2
42
0
Order By: Relevance
“…Finally, the residue on the sieves was collected, dried at 60 • C, and weighed (Sainju et al, 2003). The total SOC and SOC associated with water-stable aggregates were determined through oxidation with potassium dichromate and external heating (Bao, 2005).…”
Section: Sample Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the residue on the sieves was collected, dried at 60 • C, and weighed (Sainju et al, 2003). The total SOC and SOC associated with water-stable aggregates were determined through oxidation with potassium dichromate and external heating (Bao, 2005).…”
Section: Sample Collection and Analysismentioning
confidence: 99%
“…SOC is a binding substance imperative for the formation of aggregate structures (Cerdà, 2000;Wu et al, 2004). Land cover significantly affects SOC contents by influencing the input and output of the organic matter in soil and, therefore, the distribution and stability of soil aggregates (Powers, 2004;Luo et al, 2011;Arjmand et al, 2015). After vegetation restoration, the organic carbon contents, MWD, and GMD of the WSAs > 0.25 mm increased, and the PAD and D values decreased.…”
Section: Effects Of Vegetation Restoration On the Distribution And Stmentioning
confidence: 99%
“…46, 50.03, 72.02, 63.21, 66.63, and 44.47% of the total splash erosion. Arjmand Sajjadi and Mahmoodabadi (2015) performed raindrop splash experiments using rainfall intensities of 57 and 80 mm h -1 and showed that the transport of fine particles <0.043 mm was greater than the transport of larger particles under high rainfall intensity. This conclusion is consistent with the conclusion presented by Meyer et al (1980).…”
Section: Splash Detachment Of Aggregate Fragments Under Different Raimentioning
confidence: 99%
“…PSD affects the movement and retention of water, solutes, heat, and air, and thus greatly affects soil properties (Arjmand Sajjadi et al, 2015 Fig. 3.…”
Section: Particle-size Distribution (Psd)mentioning
confidence: 99%